The drive-in, the supermarket, and the transformation of commerical space in Los Angeles, 1914-1941 - Longstreth, Richard W. (MIT Press, 1999)
Richard Longstreth is one of the few architectural historians to focus on ordinary commercial buildings - buildings usually associated with commercial builders and real estate developers rather than architects and thus generally overlooked by historians of "high" architecture.